Evaluation of Impact of Some Pulse Parameters on the Efficiency of Electric Cardiac Defibrillation - I. V. Venin; M. S. Bogushevich; A. I. Redko; S. V. Serikov (Общая реаниматология)
Objective: to test the hypothesis of the resonance pattern of an electric cardiac defibrillation process and to study the impact of the frequency spectrum of pulses of various shape on the efficiency of defibrillation.Material and methods. The frequency spectrum of pulses the efficiency of which during defibrillation was known was examined. Delta pulses with a steep anterior and flat posterior front; a pulse with a flat anterior and steep posterior front, a bipolar asymmetric trapezoidal pulse from a DKI-H-15 St BIFASIK+ defibrillator, and its returning pulse were considered. The pulse spectra were calculated and plotted using the Mathematica program (Wolfram Research Inc.).Results. The different pattern of a relationship of the efficiency of defibrillation to the duration of pulses with a damping increment or decrement is shown to be contradictory to the hypothesis of the resonance pattern of an electric cardiac defibrillation process. The pulses with the equal frequency spectrum may have a great efficiency difference during defibrillation. The efficiency may be affected by the pulse phase interval.Conclusion. The value of a spectrum module at the zero frequency of pulse phases may be regarded as one of the parameters characterizing the efficiency and safety of defibrillation exposure.